IMPROVING STUDENTS’ SPEAKING SKILLS IN ASKING AND GIVING INFORMATION BY USING INFORMATION GAP - Laelasari, Ela; Apriliaswati, Rahayu; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was aimed to know how Information Gap Activities improved students? speaking in asking and giving information on the Seventh Grade Students of SMP Adisucipto in Academic Year 2016/2017. The research was conducted using Classroom Action Research in three cycles. The research participants were the English teacher and 14 students of the Seventh Grade. The data were collected through field notes, students? speaking performance, and teacher?s interview. The results showed that students? speaking skills in asking for and giving information improved from cycle 1 to cycle 3. Students? vocabulary improved through preparation of information gap, dividing students into two groups, and forming pairs to find required information supported by other strategies such as using pictures, using a shopping catalogue, sorting information from text, and using grid. Students? ability in asking questions of specific information improved through preparation of Information Gap Activities and forming pairs to find required information supported by other strategies such as introducing questions-answers together and using grid. Meanwhile, students? activeness improved through all of the steps in Information Gap Activities. Forming pairs to find required information gave the students chances to practice their speaking skill in asking and giving Information which improved students? willingness to speak and reduces students? shyness.Keywords:     Information gap activities, asking for and giving information, speaking.